Pengembangan Media Kincir Perkalian untuk Meningkatkan Minat Belajar Siswa pada Pembelajaran Matematika Perkalian Dasar Kelas IV SD Negeri 06 Pontianak Timur - Yusin, Latipah; Fatmawati, Risdiana Andika; Suriyana, Suriyana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The aim of this research is to produce a multiplication wheel media product to increase the learning interest of fourth grade students at SD 06 East Pontianak. This research includes the development of Research and Development (R&D) with the ADDIE development model developed by Dick and Carry consisting of five steps, including (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The development of this learning media was validated by media experts and material experts. The validation results from all experts show that the development of this multiplication wheel learning media is very feasible, practical and effective for use in class IV elementary schools. This is proven by validation from media experts and material experts as well as student responses and effectiveness trials on students (measured by interest questionnaire questions). The average percentage of media experts is 92% in the